The association of motives with problematic smartphone use: A systematic review - Beau Mostyn Sullivan; Amanda M. George (Cyberpsychology: Journal of Psychosocial Research on Cyberpspace, 2023)
Motives for smartphone use may be key factors underlying problematic smartphone use (PSU). However, no study has reviewed the literature investigating the association of motives with PSU. As such, we conducted a systematic review to: (a) determine which smartphone use motives were associated with PSU; and (b) examine the potential indirect and moderating effects of motives in the relationship of psychosocial factors with PSU. We identified 44 studies suitable for inclusion in our systematic review. There was extensive heterogeneity in smartphone use motives measures across the studies, including 55 different labels applied to individual motives dimensions. Categorisation of these motives based on their definitions and item content identified seven motives that were broadly assessed across the included studies. Motives which reflected smartphone use for mood regulation, enhancement, self-identity/conformity, passing time, socialising, and safety were generally positively associated with PSU. There were indirect effects of depression, anxiety, and transdiagnostic factors linked to both psychopathologies on PSU via motives, particularly those reflecting mood regulation. Stress and anxiety variously interacted with pass-time, social, and a composite of enhancement and mood regulation motives to predict PSU. However, the heterogeneity in the measurement of smartphone use motives made it difficult to determine which motives were most robustly associated with PSU. This highlights the need for a valid and comprehensive smartphone use motives measure.